(untitled) (LEARNing Landscapes, 2012)
In this study we discuss how disorienting experiences in informal learning contexts promote cross-cultural awareness in preservice teachers during a study abroad program to Honduras. We used interpretive phenomenology via semi-structured interviews to examine how nine preservice teachers made sense of their experiences studying abroad. We found that immersing preservice teachers in informal learning contexts and diverse cultural settings other than their own fosters new socio-cultural insights in relation to their roles as future educators.